Berbahasa Inggris Melalui Teater Wayang - Eddy Pursubaryanto (Institut Seni Indonesia Surakarta, 2007)
This article presents an example of how a script of Wayang Kulit in English version is used to provide more English exposure for English learners. It offers a strategy for English instructors and anyone who is learning English.